GREM1 is a novel serum diagnostic marker and potential therapeutic target for pancreatic ductal adenocarcinoma - Yang, Sen; Zhang, Yalu; Hua, Yuze; Cui, Ming; Wang, Mengyi; Gao, Junyi; Liu, Qiaofei; Liao, Quan (Frontiers in Oncology, 2022)
Objective: Pancreatic ductal adenocarcinoma (PDAC) is a highly malignant neoplasm with rising incidence worldwide. Gremlin 1 (GREM1), a regulator of BMP signaling, finetunes extensive biological processes, including organ morphology, cellular metabolism, and multiple pathological developments. The roles of GREM1 in PDAC remain unknown. Methods: Varieties of public databases and online software were employed to analyze the expressions at transcription and protein levels of GREM1 in multiple malignant neoplasms including PDAC, and in addition, its potential pro-tumoral functions in PDAC were further evaluated. A total of 340 serum samples of pancreatic disease, including PDAC, low-grade malignant pancreatic neoplasm, benign pancreatic neoplasm, pancreatitis, and 132 healthy controls, were collected to detect GREM1. The roles of serum GREM1 in diagnosis and prediction of survival of PDAC after radical resection were also analyzed. Results: Bioinformatic analyses revealed that GREM1 was overexpressed in PDAC and predicted a poorer survival in PDAC. Higher protein level of GREM1 in PDAC correlated with stroma formation and immunosuppression by recruiting varieties of immunosuppressive cells, including T regulatory cells (Treg), M2 macrophages, and myeloid-derived suppressor cells (MDSCs), and exhausted T cells into the tumor microenvironment. Higher level of serum GREM1 was observed in PDAC patients, compared to healthy control (p＜0.001). Serum GREM1 had a good diagnostic value (AUC = 0.718, p＜0.001), and its combination with CA-199 achieved a better diagnostic efficacy (AUC=0. 914, p＜0.001 ), compared to CA-199 alone. The cut-off value was calculated by ROC analysis and PDAC patients were divided into two groups of low- or high-GREM1. Logistic analyses showed serum GREM1 positively correlated with tumor size (HR=7.097, p = 0.032) and histopathological grades (HR = 2.898, p = 0.014). High-level serum GREM1 (1117.8 pg/ml) showed a shorter post-operative survival (p=0.0394). Conclusion: Higher intra-tumoral expression of GREM1 in PDAC contributes to tumor stroma and immunosuppressive tumor microenvironment, presenting its therapeutic potential. High-level serum GREM1 predicts poorer survival after resection. Combination of serum CA-199 and GREM1 shows a stronger diagnostic efficacy in PDAC.